PENDAMPINGAN PERHITUNGAN HARGA POKOK PRODUKSI PADA UMKM SERBUK JAHE DESA KARANG INDAH, BARITO KUALA - Salman, Putriana; Pebriadi, Muhammad Syahid; Rahmawati, Ningtyas; Utami, Nadia Puteri (LPPM Universitas Bina Bangsa, 2024)
One of the problems with MSMEs Serbuk Jahe Merah in Karang Indah Village, Barito Kuala District, is the difficulty of calculating the cost of production. The selling price is set based on simple calculations and comparison with competitor prices. The solution to this problem is to provide assistance in calculating the cost of production which will later be used as the basis for determining the selling price. The methods used in this activity are providing material by resource persons, assistance in calculating the cost of production and evaluation in the form of pre-tests and post-tests. Overall, this activity received a positive response from partners. This can be seen from the partners enthusiasm when filling out the worksheet for calculating the cost of production and during questions and answer. From the evaluation results, it is known that partners understanding of the cost of production increased by 41.8%, partners ability to classify production costs increased by 91.5% and partners skills in calculating the cost of production increased by 85%.